Mucosal exfoliation as a selective reaction to etoricoxib. (31st August 2016) - Patanè, M.; Isola, S.; Gangemi, S.; Minciullo, P. L.
Summary: What is known and objective: Etoricoxib is a non‐steroidal anti‐inflammatory drug (NSAID) that inhibits the inducible cyclooxygenase (COX‐2) with a good safety profile. We describe the first case of two mucosal adverse events to etoricoxib in the same patient. Case description: Our patient developed stomatitis with mucosal exfoliation after etoricoxib assumption. Some months later, after a new etoricoxib intake, she presented with vaginal burning, tongue angioedema and erosions, oral exfoliation and wheals on the hands. A provocation test with diclofenac was negative. What is new and conclusion: The peculiarities of our case are the rare clinical manifestation and the selective hypersensitivity to COX‐2 inhibitor with tolerance to a non‐selective NSAID. Abstract : Tongue angioedema with erosions and exfoliation of the oral mucosa as a selective hypersensitive reaction to COX‐2 inhibitor.